2007
DOI: 10.1002/qua.21427
|View full text |Cite
|
Sign up to set email alerts
|

Approximate MCSCF optimization for multiconfigurational spin‐tensor electron propagator method (MCSTEP): The vertical ionization potentials of CO, HCN, HNC, H2CO, and O3

Abstract: ABSTRACT:The multiconfigurational spin tensor electron propagator method (MCSTEP) was developed as an implementation of electron propagator/single particle Green's function methods. MCSTEP was specifically designed for open shell and highly correlated (nondynamically correlated) initial states. The initial state used in MCSTEP is typically a small complete active space (CAS) with multiconfigurational self-consistent field (MCSCF) state. In some cases, because of our use of a small CAS in MCSTEP, the Lagrangian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Current work in our laboratory includes combining complex‐scaled electron‐nuclear attraction integral evaluation subroutine to our CMCSCF codes with application of the M 1 method to study shape, Auger and Feshbach resonances of molecules of chemical and physical interest. In addition, we are developing ways to determine the resonance positions and widths accurately using CMCSCF‐based electron propagator method (CMCSTEP) that utilizes the full M matrix, since MCSTEP does not use single determinant‐based perturbation theory and has been shown to give highly reliable IPs and EAs for atoms and molecules including open shell and highly correlated systems 30–32, 50–56.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current work in our laboratory includes combining complex‐scaled electron‐nuclear attraction integral evaluation subroutine to our CMCSCF codes with application of the M 1 method to study shape, Auger and Feshbach resonances of molecules of chemical and physical interest. In addition, we are developing ways to determine the resonance positions and widths accurately using CMCSCF‐based electron propagator method (CMCSTEP) that utilizes the full M matrix, since MCSTEP does not use single determinant‐based perturbation theory and has been shown to give highly reliable IPs and EAs for atoms and molecules including open shell and highly correlated systems 30–32, 50–56.…”
Section: Discussionmentioning
confidence: 99%
“…Multiconfigurational spin tensor electron propagator (MCSTEP) is a very powerful tool for calculating accurate ionization potentials (IPs) and electron affinities (EAs) including open shell atoms and molecules that have nondynamical correlation in their initial (or reference) states 30–32, 50–56. It involves solving for IPs/EAs (ω f ) from the following eigenvalue equation 30: $\underline {\underline M}$ has five nonzero blocks and each one involves a combination of tensor operators.…”
Section: Theorymentioning
confidence: 99%
“…We showed earlier that the operator manifold {ai,ai} ${\{{a}^{i},{a}_{i}\}}$ for a multiconfigurational EP defined in terms of a complex scaled Hamiltonian can reproduce the resonance positions and widths for simple (shape) resonances very well [80,175,176] . Those were motivated by the work of Yeager and co‐workers on multiconfigurational electron propagator for the determination of ionization potential (IP) and electron affinity (EA) of highly correlated systems [294–305] . They had observed that the most dominant contribution to the EP/EA comes from the part of the EP involving simple electron attachment ( a i ) and detachment operators ( a i ).…”
Section: Methodsmentioning
confidence: 99%